MARKETING MIX (BAURAN PEMASARAN) TEH DAUN KELOR BEN ALI MORINGA (Studi Kasus: CV. Atlantic, Di Desa Tanjung Ara, Kecamatan Tanah Jambo Aye, Kabupaten Aceh) - Rabiatun Adawiyah; Faoeza Hafiz Saragih; Cut Gustiana (Politeknik Pertanian Negeri Kupang, 2023)
It was necessary to introduce Moringa leaf as a herbal medicine that gives a healthy benefit. The aim of this study was to apply the marketing mix of Ben Ali Moringa leaf tea to achieve maximum profit. Primary data was obtained by observation, interviews, and questionnaires, the sample was the deputy director of CV Atlantic and moringa tea consumers. The sampling technique used the case method and a descriptive qualitative. The results showed that the product diversity is less varied. In quality, there is no BPOM and halal certification from the Indonesian Ulema Council. On the style of the brand that is less prominent and the size is less varied. Ben Ali Moringa leaf tea pricing pays more attention to direct factors. The promotion has not implemented a clear strategy, and the distribution channel was small. To deliver tea using commercial shipping services the costs are still borne by consumers. Key Words: Strategy, Marketing, Marketing, Moringa.